If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = t + 8 Reorder the terms: -4 = 8 + t Solving -4 = 8 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -4 + -1t = 8 + t + -1t Combine like terms: t + -1t = 0 -4 + -1t = 8 + 0 -4 + -1t = 8 Add '4' to each side of the equation. -4 + 4 + -1t = 8 + 4 Combine like terms: -4 + 4 = 0 0 + -1t = 8 + 4 -1t = 8 + 4 Combine like terms: 8 + 4 = 12 -1t = 12 Divide each side by '-1'. t = -12 Simplifying t = -12
| -5+33=7 | | -7r-8=14 | | -5+48=7 | | 3(y-9)4=-2y | | 4z-43=2z+80 | | 4(2z-8)-(z-9)=8(8-7z) | | -5+36=7 | | -5g+1.2=-18.8 | | 10x-186=90-2x | | 7(k+9)=9(k-5)-14 | | 3y=4(x+6) | | -(5x+8)+12=17+17 | | 4f+2= | | -7j+62=-2g+12 | | 11b^2-71b-42=0 | | 5-c-10-5c-2=8 | | M=-4m+15 | | -4x-6x=20 | | Y=-1x+5 | | 8x+x-5=40 | | .4x+.4=g | | 1.4x-3.5=0.6x-2.54 | | 4+7f=f+16 | | 1+5x=7+3x | | (2x+3)(x+k)=0 | | 3(4r-5)-36= | | 4+7f=x+16 | | 8x+1.2=-70 | | 30n-40=-41+3n | | 4-7f=f+16 | | .25x-3=x+8 | | 2r-(3.1)=1.7 |